Histomorphological study of the spleen in indigenous Gazelle (Gazella subgutturosa): M. H. Abed Muslih and S. M. Mirhish - Mirhish, S. M. (The Iraqi Journal of Veterinary Medicine, 2018)
The study aimed to investigate the anatomical and histomorphometrical features of spleen in gazelle. To achieve this goal, spleens of 7 animals were used. The gross aspect of the study revealed that the spleen of gazelle appeared dark brown in color with elliptical shape and was situated at the left lateral surface of the rumen. It occupied the area extended from the 8th rib to 11th rib. Length and width of the spleens were calculated and the mean were 7.94±0.1, 5.88±0.2 respectively. There were three ligaments connected the spleen with adjacent structures, namely splenogastric, splenorenal and splenophrenic. The blood supply of the spleen was studied using X-rays and resin injection methods. The splenic artery was divided into three primary branches, each one subdivided into two secondary branches. The latter branched into tertiary branches which were distributed all over the splenic parenchyma. Microscopic findings showed that the capsule of spleen in gazelle was composed from of two layers, the outer one made of mainly of dense connective tissue; whereas the inner layer of capsule consisted of connective tissue fibers in addition to abundance of smooth muscle fibers interweaving among them. The total mean thickness of the capsule was 210.51+8.3 µm. The splenic parenchyma in gazelle consisted of white pulp represented by lymphoid follicles with their marginal zones and periarterial lymphatic sheath while the red pulp represented by splenic cords and sinusoids. The area of white pulp in the gazelle comprised about 9.6% of the spleen parenchyma. Red pulp composed mainly from cords of connective tissue and small sinuses or sinusoids filled with blood cellular element which extended among these cords and was lined by flattened endothelial cells with relatively large spaces or slits between them. The sinusoids were found to be lymphocytes, reticular, plasma, macrophages and occasional megakaryocytes whereas the megakaryocyte appeared large with acidophilic cytoplasm and dark elongated multilobated nucleus. This research work was performed in order to establish the basic histomorphological information helpful for the veterinary medical practice and veterinary surgions to developing their work on gazelle like designing the approach of some surgical operations like spleenectomy or any surgical entrance may be needed in these animal species.